Thromboplastin Calibration - Loeliger, E A; Hoeff-van Halem, R. van der; Halem-Visser, L P van (Thrombosis and Haemostasis, 1978)
Standardization of the thromboplastin most commonly used for anticoagulant control in The Netherlands has been achieved by the Dutch Reference Laboratory for Anticoagulant Control. The system established for control indicates the performance characteristics of each batch of thromboplastin in patients relative to a national calibration batch. Calibration constants were assessed according to an ICTH/ICSH proposal and with a reproducibility of approximately 2% (CV). With the use of a given calibration constant of the International Reference Preparation of Thromboplastin (1.0) and after assessment of the calibration constant of the National Reference Preparation in international terms (0.93), the accuracy of calibration with the various modifications of the calibration procedure is of the order of magnitude of 3% (CV). On the basis of the calibration protocol, physicians will be provided with correlation tables containing, for their convenience, prothrombin (thromboplastin) times in terms of the reference thromboplastin (uniform, i. e., batch-independent, prothrombin times), conventional prothrombin activity (percentages), and in due course with International Calibrated Ratios.* With this approach current practice in the prescription of oral anticoagulants will be maintained. Opportunity is given, however, to aim at internationally proposed therapeutically optimal target values.